2010
DOI: 10.1111/j.1365-2125.2010.03619.x
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing pattern of anti‐epileptic drugs in an Italian setting of elderly outpatients: a population‐based study during 2004–07

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• In the last years there has been a growing trend in anti-epileptic drug (AED) use, particularly in elderly patients, but few data concerning indication of use are available in general practice.• Various AEDs, including newer agents, have been approved for indications other than epilepsy and are increasingly also used for unlicensed indications.• No data about the impact of re-imbursement restrictions on the choice of anti-epileptic drugs in general practice are availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 30 publications
1
43
1
Order By: Relevance
“…It is possible that one of the reasons for the widespread use of tramadol is that UK GPs and possibly patients perceive it as being weaker than other strong opioids. Previous studies have also identified increasing volumes of different classes of analgesics prescribed; for instance, the prescribing volumes of AEDs increased in Denmark between 1993 and 2002 (Tsiropoulos et al, 2006), and in Italy, between 2004(Oteri et al, 2010, as in our study. However, although tramadol may present somewhat fewer concerns about dependence than some other strong opioids, it is particularly likely to lead to toxicity in overdose as a result of its dual action at both opioid and serotonin/ norepinephrine receptors, the latter not blocked by naloxone (BNF, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…It is possible that one of the reasons for the widespread use of tramadol is that UK GPs and possibly patients perceive it as being weaker than other strong opioids. Previous studies have also identified increasing volumes of different classes of analgesics prescribed; for instance, the prescribing volumes of AEDs increased in Denmark between 1993 and 2002 (Tsiropoulos et al, 2006), and in Italy, between 2004(Oteri et al, 2010, as in our study. However, although tramadol may present somewhat fewer concerns about dependence than some other strong opioids, it is particularly likely to lead to toxicity in overdose as a result of its dual action at both opioid and serotonin/ norepinephrine receptors, the latter not blocked by naloxone (BNF, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…The rapid introduction is in agreement with what was reported in a study from Italy, but in contrast to the findings from Norway . There is no single clear determinant of a country's level of drug usage and the introduction may be influenced by a number of factors such as the extent of prescribing restrictions, the nature of pharmaceutical marketing activity, the existence of health technology assessment processes, the existence of initiatives to influence prescribing practice, clinical attitudes and culture, the extent of research activity and differences in incidence, prevalence of the disease or unmet clinical needs .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown the protective effect of hydroalcoholic extract of fruit of Z. jujuba against pentylenetetrazole and maximal electroshock-induced seizures, oxidative stress, and cognitive impairment in rats [8]. Phenytoin, phenobarbitone, and carbamazepine are the first line drugs used for the management of generalized tonic-clonic seizures [12,13]. The safety and efficacy profile of these drugs are well documented.…”
Section: Introductionmentioning
confidence: 98%